Dark Ocean - Wise, K; Kratz, S (Dark MOFO, 2016)
Dark Ocean was an interdisciplinary exhibition that presented work by artists and scientists who shared an interest in representing the ocean. Installed at the Institute for Marine and Antarctic Science, University of Tasmania as part of Dark MOFO 2016, the exhibition explored how art and science address visualisation, here focusing on the dynamics of the marine environment. The curatorial project extended Wises ongoing research into interdisciplinary approaches to the medium, politics and representation of the ocean.